Expected Value of the Maximum of Two Quantities

Among his 2018 2018 guests, Keith chooses a random subset of people to attend his super secret mathematics-themed party. Let X X be the number of people Keith chooses. Also, let M M be the expected value of max { 0 , X 1009 } \text{max}\{0, X - 1009\} .

If M M can be expressed in simplest form as p q , \frac{p}{q}, compute the number of 2 2 's in the prime factorization of p q pq plus 7. 7.


The answer is 2019.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Alan Yan
Apr 22, 2018

We let n = 1009 n = 1009 , and Y = max { 0 , X n } Y = \max \{ 0, X - n\} . It is clear that E [ Y ] = k = 0 n k ( 2 n n + k ) 2 2 n . \mathbb{E}[Y] = \frac{\sum_{k = 0}^n k \binom{2n}{n+k}}{2^{2n}}. But, observe that from Cauchy's Residue Theorem, ( 2 n n + k ) = 1 2 π i d z ( 1 z ) n + k + 1 z n k + 1 \binom{2n}{n+k} = \frac{1}{2\pi i} \oint \frac{dz}{(1-z)^{n+k+1} z^{n-k+1}} where we integrate along z = ε |z| = \varepsilon . Summing this for all k 0 k \geq 0 , we get k = 0 n k ( 2 n n + k ) = 1 2 π i 1 ( 1 z ) n + 1 z n + 1 k = 0 k z k ( 1 z ) k d z = 1 2 π i 1 ( 1 z ) n + 1 z n + 1 z / ( 1 z ) ( 1 z / ( 1 z ) ) 2 d z = 1 2 π i d z ( 1 z ) n z n ( 1 2 z ) 2 \begin{aligned} \sum_{k = 0}^n k \binom{2n}{n+k} & = \frac{1}{2\pi i} \oint \frac{1}{(1-z)^{n+1}z^{n+1}} \cdot \sum_{k = 0}^\infty \frac{kz^k}{(1-z)^k} dz \\ & = \frac{1}{2\pi i} \oint \frac{1}{(1-z)^{n+1}z^{n+1}} \cdot \frac{z/(1-z)}{(1 - z/(1-z))^2} dz \\ & = \frac{1}{2\pi i} \oint \frac{dz}{(1-z)^n z^n (1-2z)^2} \end{aligned} For ε \varepsilon sufficiently small, the image of z = ε |z| =\varepsilon under z z ( 1 z ) z \to z(1-z) forms a nice closed path around 0 0 . So, let w = z ( 1 z ) w = z(1-z) , which means that z = ( 1 1 4 w ) / 2 z = (1 - \sqrt{1 - 4w})/2 and ( 1 2 z ) 2 = 1 4 w (1-2z)^2 = 1-4w . So, changing our variable of integration to be w w , our sum becomes 1 2 π i d w w n ( 1 4 w ) 3 / 2 = [ w n 1 ] ( 1 4 w ) 3 / 2 = ( 4 ) n 1 ( 3 / 2 n 1 ) = n 2 ( 2 n n ) . \frac{1}{2\pi i} \oint \frac{dw}{w^n (1-4w)^{3/2}} = [w^{n-1}] (1-4w)^{-3/2} = (-4)^{n-1} \binom{-3/2}{n-1} = \frac{n}{2} \binom{2n}{n}. So, E [ Y ] = n 2 2 n + 1 ( 2 n n ) \mathbb{E}[Y] = \frac{n}{2^{2n+1}} \binom{2n}{n} . We can check that ( 2 n n ) \binom{2n}{n} has 7 7 factors of 2 2 . So the answer is 2 n + 1 = 2019 2n+1 = \boxed{2019} .

Remark We could've have gotten the sum in the following quicker but more boring way k = 0 n k ( 2 n n + k ) = k = 0 n ( n + k ) ( 2 n n + k ) n k = 0 n ( 2 n k ) = 2 n k = 0 n ( 2 n 1 n + k 1 ) n ( 1 2 ( 2 n n ) + 2 2 n 1 ) = 2 n ( ( 2 n 1 n ) + 2 2 n 2 ) n ( 1 2 ( 2 n n ) + 2 2 n 1 ) = n 2 ( 2 n n ) . \begin{aligned} \sum_{k = 0}^n k \binom{2n}{n+k} & = \sum_{k = 0}^n (n+k) \binom{2n}{n+k} - n \sum_{k = 0}^n \binom{2n}{k} \\ & = 2n \sum_{k =0 }^n \binom{2n-1}{n+k-1} - n \left ( \frac{1}{2} \binom{2n}{n} + 2^{2n-1} \right )\\ & = 2n \left ( \binom{2n-1}{n} + 2^{2n-2} \right ) - n \left ( \frac{1}{2} \binom{2n}{n} + 2^{2n-1} \right ) \\ & = \frac{n}{2} \binom{2n}{n}. \end{aligned}

Insightful Alan! Thanks for this stunning one liner solution :)

Haveesh Viswanatha - 3 years, 1 month ago

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...